The Integrated Dynamic Self-Sufficiency (IDSS) Framework: A Literature- Informed Conceptual Model for Sustainable Community Development - Peter G. Narsico (Future Science / FSH-PH Publications, 2026)
Often, interventions to build community development fail to achieve durable self-sufficiency because support is fragmented or withdrawn before local capacities have been stabilized. In this paper we present the Integrated Dynamic Self-Sufficiency (IDSS) Framework. This model was developed using reflective conceptual reasoning and then examined and refined through an integrative, interdisciplinary review. The preliminary model organized self-sufficiency around five interrelated elements: Purpose, Mindset, Competence, Resources, and Connection. We drew on literature from community development, resilience studies, psychology, education, sustainable development and systems thinking to illuminate the elements, evaluate their conceptual fit and refine the dynamic relationships of the model. In the framework, the elements move toward or away from a central state of self-sufficiency, and the strength of their connections represent the degree of integration and stability. The model identifies two possible ways it could fail: either it only addresses a subset of the elements, or it removes external support before sufficient convergence has occurred. It thus promotes a phased intervention logic where support is modulated to local capacity and scaled down responsibly as self-sufficiency is built. As a literature-informed conceptual model, the IDSS Framework offers testable propositions and potential applications in education, disaster relief, social services, and work with marginalized communities.